Predicting Universal Healthcare Through Health Financial Management for Sustainable Development in BRICS, GCC, and AUKUS Economic Blocks - M. V., Manoj Kumar; Sastry, Nanda Kumar Bidare; Moonesar, Immanuel Azaad; Rao, Ananth (Frontiers in Artificial Intelligence, 2022)
It is evident that the majority of people worldwide still struggle to get primary health care facilities. Universal Health Coverage (UHC) proposes access to high-quality, affordable primary healthcare for all. UN 17 SDG goals are expected to be executed and achieved by all 193 countries through national sustainable development strategies and multi-stakeholder partnerships. This paper addresses SDG 3.8 - access to good quality and affordable healthcare and two sub-indicators related to societal impact (SDG 3.8.1 and SDG 3.8.2) through two objectives. The first objective is to determine whether HEI drive UHC; and the second objective is to analyze the importance of key determinants and their interactions with UHC in three economic blocs: emerging GCC vis-à-vis developed AUKUS. We use the WHO Global Health Indicator database and UHC periodical surveys to evaluate the hypotheses. We apply the state-of-the-art Machine Learning (ML) models and OLS (traditional - Ordinary Least Square regression) methods to see the superiority of AI over traditional ones. The ML Random Forest Tree Method is found to be superior to the OLS model in terms of least RMSE (Root Mean Square Error). The ML results indicate that PVT-D, Out-of-Pocket Expenditure (OOPS) per Capita in US$, and Voluntary Health Insurance (VHI) as a percent of Current Health Expenditure (CHE) are the key factors influencing UHC across the three economic blocs. Our findings have implications for drafting health and finance sector public policies such as providing affordable social health insurance to the weaker sections of the population, making insurance premiums less expensive and affordable by the masses, designing health care financing policies beneficial to the masses. Universal health coverage is an important determinant for health for all and requires an in-depth analysis of the factors related. The policymakers are often faced with the challenge to prioritize the economic needs of sectors such as education and food safety, making it difficult for health care to receive its due share. In this context, the present paper attempts to identify the key components influencing the attainment of universal health coverage that may enable the policy changes to address the same more effectively and efficiently.